Legal Responsibility Of Land Use Rights Holders For Land Conversation That Violates The Social Function Of Land Rights - Fauziah, Rachmah (Universitas Negeri Semarang, 2026)
This study aims to examine in depth how positive agrarian law qualifies the conversion of land use rights (HGU) that violate the social function of land rights. In addition, this study also aims to formulate an ideal legal accountability model for HGU holders in order to uphold social functions and prevent public losses. A normative juridical method was used in this study, which included a statute approach, a conceptual approach, and an analytical approach. The data sources consisted of primary, secondary, and tertiary legal materials, and the analysis was conducted qualitatively and prescriptively. The results of the study show that the conversion of HGU land, whether through active actions or negligence in supervision, causes environmental damage and public losses. This can be considered a violation of the social function of land rights, as stipulated in Article 6 of the UUPA and reinforced by PP No. 18 of 2021 and PP No. 20 of 2021. However, current law enforcement often stops at administrative sanctions without adequate recovery mechanisms. Therefore, a substantive accountability model is needed that includes compensation and environmental restoration mechanisms as well as administrative sanctions for revocation of rights.